The risk of ergonomic injury across surgical specialties - Aaron, Ksenia A. (PLoS One, 2021)
Lack of ergonomic training and poor ergonomic habits during the operation leads to musculoskeletal pain and affects the surgeon’s life outside of work. The objective of the study was to evaluate the severity of ergonomic hazards in the surgical profession across a wide range of surgical subspecialties. We conducted intraoperative observations using Rapid Entire Body Assessment (REBA) score system to identify ergonomic hazards. Additionally, each of the ten surgical subspecialty departments were sent an optional 14 question survey which evaluated ergonomic practice, environmental infrastructure, and prior ergonomic training or education. A total of 91 surgeons received intraoperative observation and were evaluated on the REBA scale with a minimum score of 0 (low ergonomic risk <3) and a maximum score of 10 (high ergonomic risk 8–10). And a total of 389 surgeons received the survey and 167 (43%) surgeons responded. Of the respondents, 69.7% reported suffering from musculoskeletal pain. Furthermore, 54.9% of the surgeons reported suffering from the highest level of pain when standing during surgery, while only 14.4% experienced pain when sitting. Importantly, 47.7% stated the pain impacted their work, while 59.5% reported pain affecting quality of life outside of work. Only 23.8% of surgeons had any prior ergonomic education. Both our subjective and objective data suggest that pain and disability induced by poor ergonomics are widespread among the surgical community and confirm that surgeons rarely receive ergonomic training. Intraoperative observational findings identified that the majority of observed surgeons displayed poor posture, particularly a poor cervical angle and use of ergonomic setups, both of which increase ergonomic risk hazards. This data supports the need for a comprehensive ergonomic interventional program for the surgical team and offers potential targets for future intervention.